Integrative analysis of transcriptomics and metabolomics reveals the protective effect and mechanism of salidroside on testicular ischemia-reperfusion injury - Jiang, Ya Ping; Liu, Bao Gui; Dang, Yi; Liu, Lin Jie; Pang, Yang; Bai, Xiao Dong; Sun, Feng; Kang, Tian Hong; Zhao, Zheng Hang (Frontiers in Pharmacology, 2024)
Testicular torsion is a critical urologic condition for which testicular detorsion surgery is considered irreplaceable as well as the golden method of reversal. However, the surgical treatment is equivalent to a blood reperfusion process, and no specific drugs are available to treat blood reperfusion injuries. Salidroside (SAL) is one of the main effective substances in rhodiola, which has been shown to have antioxidant and antiapoptosis activities. This study was designed to determine whether SAL exerted a protective effect on testicular ischemia-reperfusion (I/R) injury. In this study, the I/R injury model of the testes and reoxygenation (OGD/R) model were used for verification, and SAL was administered at doses of 100 mg/kg and 0.05 mmol/L, respectively. After the experiments, the testicular tissue and TM4 Sertoli cells were collected for histopathologic and biochemical analyses. The results revealed that SAL improves the structure of testicular tissue and regulates the oxidation–antioxidation system. To further understand the molecular mechanisms of SAL in treating testicular I/R injuries, transcriptomics and metabonomics analyses were integrated. The results show that the Nfr2/HO-1/GPX4/ferroptosis signaling pathway is enriched significantly, indicating that it may be the main regulatory pathway for SAL in the treatment of testicular I/R injuries. Thereafter, transfection with Nrf2 plasmid–liposome was used to reverse verify that the Nfr2/HO-1/GPX4/ferroptosis signaling pathway was the main pathway for SAL anti-testicular I/R injury treatment. Thus, it is suggested that SAL can protect against testicular I/R injuries by regulating the Nfr2/HO-1/GPX4 signaling pathway to inhibit ferroptosis and that SAL may be a potential drug for the treatment of testicular I/R injuries.